3x-43=2x-13

Simple and best practice solution for 3x-43=2x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-43=2x-13 equation:


Simplifying
3x + -43 = 2x + -13

Reorder the terms:
-43 + 3x = 2x + -13

Reorder the terms:
-43 + 3x = -13 + 2x

Solving
-43 + 3x = -13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-43 + 3x + -2x = -13 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-43 + 1x = -13 + 2x + -2x

Combine like terms: 2x + -2x = 0
-43 + 1x = -13 + 0
-43 + 1x = -13

Add '43' to each side of the equation.
-43 + 43 + 1x = -13 + 43

Combine like terms: -43 + 43 = 0
0 + 1x = -13 + 43
1x = -13 + 43

Combine like terms: -13 + 43 = 30
1x = 30

Divide each side by '1'.
x = 30

Simplifying
x = 30

See similar equations:

| y-7=8(x-6) | | 3(x+5)=ex | | 2x+1=1-3x | | y+9=-5(x+6) | | 12x^2-26=x | | 72=-84-24 | | 0.3x^2-x=0 | | 7x-9*3=5x-6 | | y+10=7(x-9) | | -8+49r^2=-4 | | 8y-12=4y+8 | | y=85+10x | | -7=1-2b-2b | | 2(x+4)=5+2x | | 44=-7f-5 | | (4x+2)+(3x+19)=180 | | 4b-8=10-3b | | 0.33x^2-x=0 | | 10n+98=-872 | | 3=1/x | | -7(-1+5v)-5v=-39+6v | | 4(2y-5)+5y=7 | | 5x+4=8x-12 | | 6x-12-2x=5x-2 | | -4=-4r+32 | | 4-5v=-46 | | -1.5=x-0.1/0.2 | | 7(v+75)=938 | | -2+6(5b-4)=7(b+4)+5b | | -22=-13r+4 | | 5r^3(2r^1/2) | | 8+10m-1=7m+21-4m |

Equations solver categories